f(-4)=-4(-4)-3 =13
g(-13)=6(13)^2+8(13)+1
=6(169)+104+1
=1014+105
=1119
2006-11-24 04:27:29
·
answer #1
·
answered by Skop 2
·
0⤊
0⤋
f(-4) = 13
g(13) = 6*13^2+8*13+1 = 1119
2006-11-24 12:46:45
·
answer #2
·
answered by ag_iitkgp 7
·
0⤊
0⤋
(g o f)(x) = g{ f(x) }
i.e. Find f(x) and substitute this value as x in the function g(x)
f(x) = -4x - 3
f(-4) = 13
-->
(g o f)(-4) = 6(13)^2 + 8(13) +1
= 1119
2006-11-24 12:35:38
·
answer #3
·
answered by ludacrusher 4
·
0⤊
0⤋
g(-4)=6(-4)^2 + 8(-4) + 1
= 6(16) -32 + 1 = 96-32+1
Apparently, f(x) is superfluous or a red herring in the question
2006-11-24 12:29:53
·
answer #4
·
answered by kellenraid 6
·
0⤊
0⤋
F(x)= -4(-4) - 3
= 13
g(x)= 6(13)^2 +8(13) +1
gof just is another way of saying g(f(x)).. and in this case it would be g(f(-4))
2006-11-24 12:33:07
·
answer #5
·
answered by elie010121 2
·
0⤊
0⤋
(g(f(-4)))??? = -4(-4) - 3
6(13)^2 + 8(13) + 1
5616 + 105
5721
or G(x) * F(x)
why dont you do your homework here
Its free
http://www.college-cram.com
2006-11-24 12:35:28
·
answer #6
·
answered by kockyguitarrockr 2
·
0⤊
0⤋
g(x)=6x^2+8x+1
gof=6(-4x-3)^2+8(-4x-3)+1
=6(16x^2+24x+9)-32x-24+1
=96x^2+144x+54-32x-24+1
=96x^2+112x+31)
gof(-4)
=96(-4)^2+112(-4)+31
=1536-448+31
=1119
2006-11-24 12:32:43
·
answer #7
·
answered by raj 7
·
0⤊
0⤋